Strategi Peningkatan Taraf Hidup Petani Trenggalek dengan Metode Pola Bagi Hasil Ternak Sapi Perah - Dwi Nirnia Ari Cahyani; Hanifatus Sahro; Sindi Arista Rahman (Jurnal Pemberdayaan Masyarakat, 2022)
The Community Partnership Program (PKM) by the implementing team from universities in the context of community empowerment through the development of a dairy cattle business which is a Priority Livestock Business in Trenggalek Regency as an effort to help improve the standard of living and the economy of rural communities . The targets achieved after PKM activities in Trenggalek Regency include 1) Reducing unemployment by empowering dairy cattle, 2) Improving the welfare and standard of living of dairy cattle business actors. The method of implementing PKM for dairy farming uses the FGD (Focus Group Discussion) method and the provision of material in the form of lectures conducted to 4 participants from each of 7 sub-districts (Bendungan, Pule, Suruh, Kampak, Karangan, Tugu, and Pogalan). The results of the PKM implementation, namely the cattle rearing model in Trenggalek Regency, were mostly carried out using the Gaduhan system. The majority of dairy cows that become partners of the Dairy Cattle Farmer Group Association in 7 Districts are Gaduhan Cattle. Community service activities carried out in the form of Extension Activities, Assistance in TMR Feeding, Milking/Lactation and Assistance in Marketing Management Activities.